Nederlands in het perspectief van uitspraakverwerving en contrastieve taalkunde - Rasier, Laurent (Lage Landen Studies, 2011)
Nederlands in het perspectief van uitspraakverwerving en contrastieve taalkunde ("Dutch from the point of view of pronunciation acquisition and contrastive linguistics") gives an overview of linguistic research carried out on Dutch by specialists from different parts of Europe. As the title suggests, the book covers two topics: (1) recent developments in the research into the pronunciation of Dutch as a second or foreign language, including research into pronunciation norms and the teaching of pronunciation; (2) recent theoretical and methodological developments in contrastive linguistics providing new insights about various cross-linguistic issues, including translation.